Python for Experimental Psychologists A Fun Way of Learning How to Code Your Experiments. - Dalmaijer, Edwin S., 1990- (New York, USA Routledge, 2025)
Python for Experimental Psychologistsequips researchers who have no prior programming experience with the essential knowledge to independently script experiments and analyses in the programming language Python. This book offers an excellent introduction, whether you are an undergraduate, a PhD candidate, or an established researcher. This updated edition is on Python 3 (the most current version). It starts by teaching the fundamentals of programming in Python and then offers several chapters on scripting experiments (displaying stimuli, obtaining and logging user input, precision timing, etc.) using the popular PsychoPy package. The remainder of the book is dedicated to data analysis and includes chapters on reading/writing to text files, time series, eye tracking, data visualisation, and statistics. Access to a companion website enriches the learning experience with colour figures, example stimuli, datasets, scripts, and a portable Windows installation of Python. This book assumes no prior knowledge, and its informal and accessible tone helps readers with backgrounds in experimental psychology and cognitive neuroscience to quickly understand Python. It serves as a useful resource not only for researchers in these fields but also for lecturers instructing on methodology and data analysis. Python for Experimental Psychologistsdemystifies programming complexities and empowers researchers to proficiently conduct experiments and analyse their results.
Keywords: Psychology, Experimental -- Data processing; Psychology, Experimental -- Research -- Computer programs; Python (Computer program language); PSYCHOLOGY / Research & Methodology; PSYCHOLOGY / Experimental Psychology; COMPUTERS / Programming Languages / Python